Finding Happiness as Chair: What the Buddha Said - Randel D. Brown; Diana Linn; Jennifer Coronado (Academic Chairpersons Conference Proceedings, 2015)
This session presents an eight point plan for surviving and thriving in one of the most complex jobs in higher education. Utilizing Buddha’s wisdom we will discuss a simple pathway for finding happiness and contentment amid the expectations of this difficult position.
Keywords: leadership; communication; equilibrium; interactions; consistency